A Cedar Cove Christmas - Macomber, Debbie (Don Mills, Ont. : MIRA, 2008)
Mother-to-be Mary Jo Wyse comes to Cedar Cove on Christmas eve to search for the father of her child. When there is no room at the local inn Grace Harding invites Mary to stay with her. When Mary goes into labor that night a young paramedic comes to her rescue and Mary's brothers, the three Wyse brothers, arrive in Cedar Cove.
Keywords: Pregnant women -- Fiction; Christmas stories; Love stories